Morgan Library - Vanhoozer, Dane, photographer (Colorado State University. Libraries, 2016)
Photo depicts the north east corner of Morgan Library on an overcast day.
This work is provided by students of HIST 580A: Digital History for use on the StoryMap project: Colorado State University's Sense of Place.
Keywords: Colorado State University; buildings; Morgan Library